Proceedings of the 21st Annual Symposium on Integrated Circuits and System Design 2008
DOI: 10.1145/1404371.1404434
|View full text |Cite
|
Sign up to set email alerts
|

A novel hardware architecture design for binary arithmetic decoder engines based on bitstream flow analysis

Abstract: This paper presents the design and implementation of a dedicated hardware architecture for binary arithmetic decoder (BAD) engines of CABAD, as defined in the H.264/AVC video compression standard. The BAD is the most important CABAD process, which is the main entropy encoding method defined by the H.264/AVC standard. The BAD is composed by tree engines: Regular, Bypass and Terminate. A large set of software experiments was made to profile each engine. Based on bitstream flow analysis a new dedicated hardware a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A large number of test-benches were developed and run to evaluate the performance of our architecture with data extracted from the reference software during the decoding process of the 440 digital video sequences listed in Section 4. For these video test-benches we observed that the two main approaches adopted can improve the throughput when compared to previous works presented in [6] and [12]. So, the potential gain for the four Bypass engines (4 BYPASS) and for the specialized context selection for significance map in regular engines (SP SIGMAP) were analyzed for each different resolution of the video sequences tested.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…A large number of test-benches were developed and run to evaluate the performance of our architecture with data extracted from the reference software during the decoding process of the 440 digital video sequences listed in Section 4. For these video test-benches we observed that the two main approaches adopted can improve the throughput when compared to previous works presented in [6] and [12]. So, the potential gain for the four Bypass engines (4 BYPASS) and for the specialized context selection for significance map in regular engines (SP SIGMAP) were analyzed for each different resolution of the video sequences tested.…”
Section: Resultsmentioning
confidence: 95%
“…It compares the solutions with two and four decoder bypass engines in the architecture and our design. The results in Table 3 indicate that the increase in the hardware costs is around 2.4% for our design and the maximum frequency decreases 1.7%, both when compared to the design proposed in [12]. A large number of test-benches were developed and run to evaluate the performance of our architecture with data extracted from the reference software during the decoding process of the 440 digital video sequences listed in Section 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it results in an extra cost of the register bank. The architectures [10][11] [12][13] [14] are based on the same concept, but after some specific extensions are capable to en-/decode HD video. In [15] sixteen cascaded regular decoding units are used for more speed up for frequent SEs.…”
Section: Parallel Hardware Acceleratorsmentioning
confidence: 99%
“…In the parallel approach the number of bins/cycle fluctuates between a certain maximum and minimum, as it depends on the type of SE. It may result in 2, 3 or even 4 bins/cycle if supported by the architecture as in [12] [14]. In the purely pipeline approach the throughput never goes above more than 1 bin/cycle, but independent of SEs it remains at 1 or close to 1 bin/cycle.…”
Section: Comparisonmentioning
confidence: 99%